Perforation of the Urinary Bladder Caused by Transurethral Insertion of a Pencil for the Purpose of Masturbation in a 29-Year-Old Female - Athanasios Bantis; Petros Sountoulides; Christos Kalaitzis; Stelios Giannakopoulos; Eleni Agelonidou; Soultana Foutzitzi; Stavros Touloupidis (Case Reports in Medicine)
The urethra is a usual site of introduction of foreign bodies for autoerotic stimulation. We present an unusual case of bladder perforation caused by foreign body that was self-inserted in the urethra and consequently slipped inside the bladder in a 29-year-old female patient with psychiatric disease. The patient was referred to our department for macroscopic hematuria and abdominal pain. Imaging studies revealed the presence of a foreign body in the pelvic area which had perforated the left lateral wall of the bladder. The foreign body was removed via open cystotomy. In psychiatric patients hematuria and pelvic pain may result from insertion of a foreign body in the bladder usually during masturbation.